A Multimodal Discourse Analysis on E-Learning Website at Universitas Terbuka - Sitti Jamilah; Edy Syarif; Nuraziza Aliah; Roihatul Millah (Journal on Education, 2023)
This study aimed at finding out the visual elements provided in the e-learning website of Universitas Terbuka. The elements include visual presentation, usability, accessability, and content. The method employed in this study was Multimodal Discourse Analysis (MDA) involving the visuals of the website as data source which is available at https://elearning.ut.ac.id/. The instrument used was visual theories which support the propositions of visual presentation, usability, accessability, and content to validate the data found. In analyzing the data, interactive analysis was used involving data condensation, data display, and data verification. The findings showed that: in visual presentation, the website portrays good presentation except for its unbalance split; in usability, the website has good extent of usability, this website has provided good navigation system and easy to understand, except for the video speed; in accessibility, all elements of accessibility are achieved well; and in concern of materials, the materials are easy to access and relevant with the learners’ need.